A new species of Lepanthes (Orchidaceae: Pleurothallidinae) from Colombia with a large and protruding column - Moreno, Juan Sebastián; Vieira-Uribe, Sebastián; Karremans, Adam P. (Lankesteriana: International Journal on Orchidology, 2017)
A new species of Lepanthes from the Western Cordillera of the Colombian Andes, characterized by similar triangular sepals with a large and protruding column, is described and illustrated. The new species is similar to Lepanthes pelorostele from Ecuador, but can be distinguished from the latter by having orange and ciliate sepals and larger petals and lip.